The Potential of Weissella confusa K2 Isolated from Longan (Dimocarpus longan) Fruit as High Exopolysaccharide-Producing Strain - Ma'unatin, Anik; Khoirumiyah, Afifatul Fitri (Bogor Agricultural University, Indonesia, 2024)
Isolation of Lactic Acid Bacteria (LAB) from various sources has previously been carried out to obtain strains that produce high of exopolysaccharide (EPS). Isolate K2, which was LAB isolated from longan (Dimocarpus longan) fruit, can produce EPS. This study aimed to identify isolate K2, and evaluated the effect of supplementation carbon sources (glucose, fructose, sucrose, and lactose) and pH of media (4, 5, 6, 7, and 8) on EPS production. Isolate K2 was identified as Weissella confusa molecularly based on 16S rDNA, the type of carbon source, and the pH of media had significant effects (P<0.05) on EPS production. W. confusa K2 produced EPS that was highest on media with the supplementation of sucrose as a carbon source and produced the lowest EPS on lactose. The amount of EPS produced by W. confusa K2 under alkaline was higher than under acidic, the highest EPS of 47.703 g/L at pH 8 and the lowest EPS at pH 4 of 1.858 g/L. The physical properties showed EPS has good solubility in water with the solubility and Water Holding Capacity (WHC) at 40.533% and 354% respectively. Based on Surface morphology of EPS with Scanning Electron Microscope (SEM) analysis, the surface structure of EPS was a porous polymer matrix. Fourier Transform Infrared Spectrophotometer (FTIR) results of EPS showed the presence of absorption bands as characteristic of carbohydrates, such as the presence of O-H, C-H, C=O, C=C, C-O-C groups, and glycosidic bonds.